2002
DOI: 10.1017/s0031182001001032
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and invasion of human skin by Schistosoma mansoni cercariae: the key-role of L-arginine

Abstract: The attachment of Schistosoma mansoni cercariae to mammalian skin is specifically stimulated by L-arginine. As L-arginine is an unsuitable signal for a specific identification of mammalian skin we examined the following 5 hypotheses to explain the advantage of the cercarial sensitivity to L-arginine. (1) A Schistosoma infection lowered the arginine concentration in the serum of mice, and this could enable the cercariae to avoid attachments to already infected mice. However, the infection did not reduce the arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 0 publications
2
40
0
1
Order By: Relevance
“…Nature of the skin stimulus -The work of Haas et al (1997Haas et al ( , 2002 and Grabe and Haas (2004) provided insight as to the nature of the skin stimulus. At the epidermal surface, arginine, ceramides and linoleic acid stimulate Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nature of the skin stimulus -The work of Haas et al (1997Haas et al ( , 2002 and Grabe and Haas (2004) provided insight as to the nature of the skin stimulus. At the epidermal surface, arginine, ceramides and linoleic acid stimulate Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These infective stages recognise their hosts via complex sequences of behavioural patterns with which they successfully respond to various environmental and host cues (Haas et al, 1997;Haas, 2003). After invasion animal parasites navigate through their host's tissues to their very specific microhabitats and some of these migrating parasitic stages can follow chemical gradients of skin and blood compounds (Haas et al, 2002). It is suggested that the high complexity, specificity and diversity of hostrecognition strategies devised by parasites are important determinants in the evolution of their life cycles.…”
Section: Plant-nematode Interactions In the Rhizospherementioning
confidence: 99%
“…Orientation of migrating schistosomula was studied using the W-chamber technique, modified from Haas et al (2002a). Briefly, the larvae penetrated agar in the central chamber (5·5 mm, height of agar 6 mm) of a three-armed cuvette.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…In experiments with D. spathaceum it had to be more highly concentrated (0.5%) and contained 300 mosmol fishringer according to Haas (1974). Penetration and full transformation into schistosomula (as demonstrated by lectin staining, and in S. mansoni in addition by the Cercarienhu¨llen reaction; see Haas et al 2002a) was stimulated by a 1 mm layer of agar (pH 7.0, 5 mM phosphate buffer) containing a fatty acid, on the upper surface of the central agar block (50 lM linoleic acid in 0.25% agar for S. mansoni and T. ocellata, 50 lM linolenic acid in 0.5% agar for D. spathaceum). Both of the fatty acids used are natural penetration stimuli for the three trematode species (Shiff et al 1972;Haas and van de Roemer 1998;Haas et al 2002b).…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation